Meeting the need: Financing to attain targets - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
COMMITMENT WITHOUT FUNDING REPRESENTS UNFULFILLED GOOD INTENTIONS. IF NUTRITION-PROMOTING ACTIONS ARE TO BE IMPLEMENTED AND TARGETS MET, they need to be financed. Financing for nutrition comes from governments (domestic), from international sources—the bilateral and multilateral aid agencies and foundations that make up the “donor” community—and from people themselves.